Cloud Computing: Secure Transmission of High Definition Videos Using Cryptographic Approach - Basha.H, Anwar; Amrit Sai, S; A, Sanjnah; M, Srimathi (International Journal of Engineering and Technology, 2018)
Cloud computing facilitates ubiquitous access to shared pool of configurable system resources and services over the Internet. Often due to shared access to this massive amount of data there is equal chances of risk. Transferring sensitive information in the form of text, audio or video, over the cloud one cannot guarantee the safety of the file. This paper assesses the effect of transmission of High Definition videos with the help of cloud-based servers that will improve the security of data being transmitted as well as enhance the quality of experience for end-users. We propose to share video contents to a selective group of people using the Time Domain Attribute based Access Control(TAAC) schema and generate keys using cryptographic method which gives the much needed protection to access these videos. Further stegnographic approaches are practised to maintain the data confidentiality.Â Â